Mangifera spp. in the Ethnoclimatology Study of Tatangar Banjar Tradition in Kalimantan - Hidayati, Eisya Hanina; Yuniati, Ratna; Lestari, Retno; Jumari, Jumari; Walujo, Eko Baroto (UIN Sunan Gunung Djati Bandung, 2024)
The biodiversity of Mangifera spp. not only supports the local economy and preserve food security but also safeguards cultural heritage through their role in ethnoclimatology studies within the Tatangar tradition of the Banjar community in Kalimantan. The Banjar community demonstrates a unique connection with nature by utilizing specific Mangifera species as crucial indicators of seasonal transitions, deeply ingrained in their cultural identity. The aim of this study is to reveal the prevalence of various Mangifera species, including endangered ones, in diverse landscapes, promoting a sustainable agroforestry system and conservation efforts. Qualitative and quantitative research methods were employed to explore and analyze Tatangar knowledge within the Banjar community in Mandiangin Barat Village, particularly its connections to climate and weather. The Banjar community further traditionally classifies Mangifera species, or known as “asam-asaman”, based on morphological traits, aiding in their interpretation of Tatangar signs. These signs, rooted in the flowering time of Mangifera trees, serve as essential climate indicators, guiding agricultural practices and influencing decisions on planting and harvesting. This local knowledge enhances agricultural resilience, enriches their cultural heritage, and underscores the intrinsic relationship between culture, nature, and sustainability in Kalimantan, making it a valuable subject for ethnoclimatological exploration